Continuing CHAAOS: Vocabulary Intervention for Students With Disabilities in Eighth Grade Who Are Also English Learners. (May 2022) - O'Connor, Rollanda E.; Sanchez, Victoria M.; Jones, Brian; Suchilt, Luisana; Youkhanna, Valencia; Beach, Kristen D.
Few studies have considered academic vocabulary interventions for students who have learning disabilities (LD) and also are English learners (EL). This research explored the effects of the third year of the Creating Habits that Accelerate Academic Language of Students (CHAAOS) vocabulary intervention for eighth-grade students who received English Language Arts instruction (ELA) in special education classes. Over 70% of student participants had LD and over half were EL. Special education teachers delivered 12 weeks of intervention spaced across 7 months to 36 students. Researchers compared outcomes on receptive and expressive measures with 17 students in business-as-usual (BAU) special education ELA. Students receiving the CHAAOS intervention learned the 48 taught words better than students in BAU conditions, retained their knowledge of words 4 weeks following the close of the intervention, and ended the year with higher vocabulary scores on a standardized measure than students in BAU classes. Students who were EL performed similarly on receptive knowledge of words to students who were native English speakers. This study documents the effectiveness of explicit vocabulary routines for students who have LD and are also EL.